Titkos háború a déli államhatár mentén az '50-es évek elején - Jakus, János (Közép-Európai Közlemények, 2012)
Following the 1948 Bucarest resolution of the COMINFORM, better known as Information Office (TI) the situation between Yugoslavia and the neighbouring peoples‟ democracies dramatically worsened. However secret data collection and network organisation between the opposing parties started much earlier. Tito was in an advantageous position concerning intelligence because in the framework of the Allied Control Commission he had a military mission working in Hungary. The representatives of the mission had fruitful relationship with important Hungarian political and military personalities. After the acceptance of the Soviet dictate mapping the foreign relationships, internal situation, industrial capacity, stocks of raw materials, and military preparedness of the country led by Tito the „main evil‟, the „dog of the imperialists‟ had an important place in the activities of the secret services of the peace camp.